Market-oriented environmental regulations, employment adjustment and transfer path: Quasi-experimental evidence from China's carbon emissions trading pilot. (1st October 2022) - Bu, Tao; Du, Wenhao; Tang, Chengxiang; Liu, Yahong; Wang, Xinyuan; Wang, Yueheng; Tang, Daisheng
Abstract: Following China's pilot program of the released Carbon Emission Trading (CET) in 2011, affected companies were forced to alter their production and operational choices, which had an impact on their labor demand and employment structure. This study examines the employment adjustment effect and employment transfer effect of CET in China using propensity score matching (PSM) and difference-in-differences (DID) method, based on the panel data of Chinese listed companies (2009–2019). We found that China's CET has expanded the scale of employment and changed the employment structure in the pilot regions. The employment adjustment effect of CET mainly comes from the First-tier pilot regions, and it mostly affects the highly educated work force. CET increased the proportion of highly-educated labor through the increase of R&D innovation and investment, while reduced the proportion of production worker employed due to the increase of production cost, it promotes the transfer of labor from underdeveloped regions to First-tier pilot regions.